2009
DOI: 10.1080/13557850903165403
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of informal care among Puerto Rican, African American, and white stroke survivors

Abstract: We find that whites, African Americans, and Puerto Ricans each have differing caregiving structures highlighted by expansion and contraction across time, size of network, and relationship to the stroke survivor. Greater cultural awareness among health professionals can lead to improved coordination of information or formal care services. These findings may also be used as a baseline for understanding the caregiving patterns of other Spanish-speaking Caribbean nations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Hispanics, who typically emphasize respect for the older people, tend to have larger family networks and are more likely to have a greater number of informal caregivers compared with whites and African Americans. 21 However, it is possible that when taking other factors into account, such as community quality and access to adequate healthcare and resources, the accrued effects of social, economic, and health disparities are not buffered by high levels of social support in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Hispanics, who typically emphasize respect for the older people, tend to have larger family networks and are more likely to have a greater number of informal caregivers compared with whites and African Americans. 21 However, it is possible that when taking other factors into account, such as community quality and access to adequate healthcare and resources, the accrued effects of social, economic, and health disparities are not buffered by high levels of social support in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Latino culture has been characterized as generally collectivist, such that Latinos often place significant value on the well-being of their family (Marin & Marin, 1991). Accordingly, caregiving structures in Latino families similarly tend to be collectivist (Dilworth-Anderson, Willians, & Gibson, 2002), and are often larger than that of White families in the United States (Hinojosa, Zsembik, & Rittman, 2009). Research with Latino caregivers has revealed strong feelings of loyalty and obligation to support nuclear and extended family members who are sick, a process that can contribute to significant "role-engulfment" (Delgado & Tennstedt, 1997;Sanchez-Ayendez, 1998;Villarreal, Blozis, & Widaman, 2005;Zea, Quezada, & Belgrave, 1994;Zsembik & Bonilla, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high levels of collectivism and family values in Latino cultures, as well as the larger size of caregiving networks among Latinos, there is an increased likelihood that Latinos will serve as family caregivers (Hinojosa, Zsembik, & Rittman, 2009). As a cultural value, familism encourages solidarity and asserts an obligation to assist both immediate and extended family members with health problems (Delgado & Tenntedt, 1997; Zsembik & Bonilla, 2000).…”
Section: Influence Of Culturementioning
confidence: 99%